Camino al chino, Contribution to the localization of Chinese textbooks for the beginners (Sinología hispánica. China Studies Review, 2021)
This presented work is the case study, which demonstrates the process of compilation,analysis and description of Chinese textbooks, titled Camino al Chino (Road to Chinese), carried outby the Confucius Institute of the University of León, and published by the McGraw-Hill Education.The creation of these textbooks was motivated after receiving various indications that the existingtextbooks had difficulties in adapting to the singularities of teaching in Spain. Therefore, this studywill try to present the principles and criteria that the authors have taken into account at the time ofpreparing and adapting these textbooks. Meanwhile, three fundamental objectives that they intendedto achieve in Spain are also mentioned: satisfying and motivating the promotion of the Chinese officialexamination, the orientation to establish their own curriculum, and diffusion of Chinese education asa second language. Finally, the authors hope that this small work will serve as an interest for futureChinese textbooks writing in Spain or other European countries and will contribute to the possibleadvancement of the localization of the language books for the beginners.